THE SEMIOTICS OF DIGITAL HUMOR: MEMES, CONTEXT, AND THE TRANSFORMATION OF THE COMIC SIGN IN SOCIAL MEDIA - Gorbatyi, Oleksandr (Global Prosperity, 2026)
The article is devoted to the study of the semiotics of digital humor, the role of memes and context in changing the comic sign in social networks. The purpose of the article is to investigate the semiotic nature of digital humor and the patterns of transformation of the comic sign in the environment of social networks through the prism of memes and context. In the course of the scientific research, general scientific methods of cognition were used, in particular, analysis, synthesis, comparison, generalization, systematization and interpretation. The results of the study show that semiotics is an important tool for explaining digital humor, but is not identified with it, since it studies a wider range of signs and sign systems. It is shown that digital humor is realized through Internet communication, is characterized by multimodality, the ability to transform and dependence on the cultural, social and platform context. It is studied that the meme is the central genre of digital humor, as it combines verbal and non-verbal stimuli, is created taking into account other memes, spreads through imitation and acquires new meanings in the process of remixing. It is concluded that the transformation of the comic sign in social networks occurs through recontextualization, intertextuality, multimodal combination of image, text, font, color and cultural codes. The study highlights the features of the formation of memes as key entertainment content in social networks. Using a semiotic approach, the perception of this information occurs differently depending on the worldview, cultural environment, circumstances, mood and general information flow. The features of the formation of a new specific black humor in the context of the coronavirus crisis are shown, where black humor, sarcasm, satire and semiotics are of particular importance in the formation of memes. All this forms the practical significance of this study, which consists in the possibility of predicting the possible perception of memes by information consumers and the formation of a toolkit of information influence on the audience by marketing agencies.